PEMANFAATAN DAUN TAHONGAI (Kleinhovia hospita L) DALAM PEMBUATAN NUGGET ITIK ALABIO SEBAGAI PANGAN FUNGSIONAL: UTILIZATION OF TAHONGAI LEAF (Kleinhovia hospita L) IN THE PRODUCTION OF ALABIO DUCK NUGGETS AS FUNCTIONAL FOODS - Manullang, Julinda; Aswita Emmawati,; Maulida Rachmawati; Servis Simanjuntak; Rafika Toding Allo (Jurnal Peternakan Nusantara, 2023)
This research was to determine the food quality of Alabio duck meat with the addition of tahongai leaves which contain antioxidants and can reduce cholesterol levels. This research was conducted at the Laboratory of Chemistry and Biochemistry of Agricultural Product Technology, Faculty of Agriculture, Mulawarman University and the Laboratory of Nutritional Biochemistry, Department of Animal Nutrition and Feed, Faculty of Animal Husbandry, Gajah Mada University for 2 months. The design used in this study was completely randomized design with 4 treatments and 4 replications. The variables observed were the quality of protein, fat and cholesterol. The results of the analysis showed that the average protein content (10.17%; 13.15%; 15.12%; and 16.83%), fat content (4.48%; 3.23%; 2.44; and 0.84%), cholesterol content (136.10gr; 123.587gr; 104.37gr; 92.26gr). The conclusion of this study is that tahongai leaves as a mixture of alabio duck nuggets can increase protein content and reduce fat and cholesterol levels as a functional food.